2001
DOI: 10.1210/endo.142.8.8343
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mRNAs and Proteins for the Na+/H+ Exchangers and Their Regulatory Factors in Baboon and Human Placental Syncytiotrophoblast

Abstract: In polarized epithelial cells of several organ systems, e.g. the kidney, a family of Na(+)/H(+) exchangers (e.g. Na(+)/H(+) exchanger-1 and -3) and their regulatory proteins, Na(+)/H(+) exchanger regulatory factor and Na(+)/H(+) exchanger-3 kinase A regulatory protein play a major role in regulating Na(+)/H(+) exchange integral to cellular homeostasis. Because the primate placenta regulates exchange of Na(+) and H(+) between the mother and fetus critical to fetal-placental homeostasis, the current study determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Isolated trophoblasts were purified by Percoll (Sigma, St. Louis, MO) gradient centrifugation. Contaminated red blood cells were eliminated by incubation of isolated trophoblasts with lysis buffer (155mM NH 4 Cl, 10mM KHCO 3 and 0.14M MDTA, pH7.2) on ice for 5 minutes.…”
Section: Trophoblast Isolation and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Isolated trophoblasts were purified by Percoll (Sigma, St. Louis, MO) gradient centrifugation. Contaminated red blood cells were eliminated by incubation of isolated trophoblasts with lysis buffer (155mM NH 4 Cl, 10mM KHCO 3 and 0.14M MDTA, pH7.2) on ice for 5 minutes.…”
Section: Trophoblast Isolation and Culturementioning
confidence: 99%
“…Emerging evidence has shown that trophoblasts are polarized epithelial cells with distinct functional regulations between the microvillous and the basal membranes (1)(2)(3)(4). For example, lactate produced by trophoblasts is a source of energy fuel to the fetus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of the decidua basalis and chorionic plate, 6-7 randomly selected sections of villous placenta were placed in phosphate buffered formalin (Sigma Chemical Co, St. Louis, MO) for immunocytochemistry and 60-70 grams of whole villous tissue used for preparation of fractions of syncytiotrophoblast MVM, cytosol presumably containing endosomes (10,000 × g; 10K), and cytosol containing endosomes and membranes contiguous with the basal membrane (BMm) and the BM/FVE as described previously [4,9]. Although we [4,13] previously showed using these procedures that alkaline phosphatase activity was enriched in the MVM and minimal in other fractions, whereas binding of dihydroalprenolol (DHAP) was enriched in the BM/FVE fraction, activity/binding was also determined in syncytiotrophoblast membrane fractions of animals of the current study.…”
Section: Animal Treatment and Tissue Collection And Preparationmentioning
confidence: 99%
“…Moreover, the specific concentrations of NHE1 and its regulatory factor NHERF1, both localized primarily to the microvillus membrane (MVM), were similar at mid and late gestation in association with a 4-fold increase in MVM alkaline phosphatase activity and presumably microvillus surface area as shown in human placenta [5,6]. Despite the physiologic importance of the placental NHE system [3,[7][8][9], our understanding of the factors controlling NHE/NHERF expression and localization in the primate syncytiotrophoblast is incomplete.…”
Section: Introductionmentioning
confidence: 99%